Relevansi Mistik Dengan Budaya Hukum Indonesia Dalam Perspektif Filsafat Ilmu - Malik (Fakultas Hukum Universitas Mulawarman, 2009)
The culture affects the law in the public. Mystical represents a science affecting human mindset, which finally emerges in the cultural form. Cultural process affects the law into law culture. Philosophically, mystical emergence in the law culture can be seen in three aspects, i.e. ontology, epistemology and axiology. The issue should be complicated when the law culture mystical may be too dominant, thus affecting public mindset, for instance, in determining the choice of law during general election, or in ascertaining the regulated law provision during the election of public representative. It possibly constrains the law development because it has to adapt with worldwide change and progress. Therefore, mystical existence as a law culture must be put in the exact position accompanying with the appropriate law confirmation when it should be a part of explicit provision, such as the regulation of santet in the Criminal Code.